Variable use of endoscopic haemostasis in the management of bleeding peptic ulcers. Issue 920 (1st June 2002) - Mahadeva, S; Linch, M; Hull, M
Abstract : Background: Randomised controlled trials (RCTs) have shown that endoscopic haemostasis is beneficial for patients with a bleeding peptic ulcer. The relevance of such data to management outside of RCTs is unclear. Therefore we examined management of patients with a bleeding peptic ulcer in a UK teaching hospital. Methods: All patients who underwent upper gastrointestinal (UGI) endoscopy for bleeding peptic ulcer between 1997 and 1999 were identified from an endoscopy database and the clinical records reviewed retrospectively. Results: A total of 872 patients underwent UGI endoscopy for presumed acute UGI haemorrhage; 179 (21%) had an endoscopic diagnosis of bleeding peptic ulcer. Seventy nine patients had a peptic ulcer with stigmata of recent haemorrhage (SRH) but only 61 (77%) of these patients received endoscopic haemostasis (77% adrenaline, 23% combination therapy). Re-bleeding occurred in 24 patients with SRH in whom transfusion requirement was the sole predictor of re-bleeding. The re-bleeding rate among patients who received adrenaline was 25% (n=12), compared with 57% (n=8) in the combination group and 31% (n=4) in those who did not receive endoscopic haemostasis. Patients who received combination endoscopic haemostasis had an increased incidence of active bleeding (p=0.007) and an increased transfusion requirement (p=0.002). Eleven of 20 patients who re-bled had repeat endoscopic haemostasis, with 45% eventually requiring surgery. Conclusions: Results of endoscopic management of bleeding peptic ulcers in the unit studied differ markedly from those published by specialised centres. The data reported here suggest that increased standardisation of endoscopic haemostasis is required, especially in units with provision for emergency "out-of-hours" endoscopy, performed by several individuals of different grades.